Systematic organisation of information in fuzzy systems - Melo-Pinto, Pedro; Teodorescu, Horia-Nicolai; Fukuda, T. (Toshio), 1948- (NATO science series. Computer and systems sciences, 2003)
This work presents new evolutions and progresses in the domain of information processing and organization in and by fuzzy systems and other types of systems using uncertain information. Also, information aggregation and organization by means of tools offered by fuzzy logic are dealt with.